Workplace Social Responsibility: The Case of five Costa Rican Companies - Hütt Herrera, Harold (2025)
Introduction: This research presents preliminary findings on theoretical and conceptual aspects, as well as practical experiences related to the management of Labor Social Responsibility. This area of work is essential for attracting and retaining the best available human talent and for fostering productivity within a healthy and inspiring work environment. Results obtained will be of great value to teaching practice.  Results will provide meaningful feedback on what is happening in companies regarding this subject, and how Public Relations Management could contribute to achieving these organizational goals. Objective: To characterize the practices implemented by five organizations in the sample to promote the well-being and development of their employees, as well as to ensure a healthy and appropriate organizational climate for the entire work team. Methodology: During this first phase of the research, a review of the most recent literature on the subject was carried out. This was complemented by semi-structured interviews with the individuals responsible for managing Social Responsibility within the organizations in the sample. [Continue reading in the article]